Can perceptuo-motor skills outcomes predict future competition participation/drop-out and competition performance in youth table tennis players? A 9-year follow-up study - Faber, I. R.; Koopmann, T.; Schipper-van Veldhoven, N.; Twisk, J.; Pion, J. (PLOS ONE, 2023)
Tools that provide a fair estimate of young table tennis players` potential and their chances to succeed will support making decisions whether to commit to an extensive development program and the accompanying lifestyle. Consequently, this study included two research questions (RQ) to evaluate the capability of the Dutch perceptuo-motor skills assessment to predict competition participation/drop-out (RQ1) and competition performance (RQ2) in young table tennis players (n = 39; 7-11 years) using a tracking period of 9 years. The perceptuo-motor skills assessment consists of eight tests assessing gross motor function (i.e., sprint, agility, vertical jump) and ball control (i.e., speed while dribbling, aiming at target, ball skills, throwing a ball and eye-hand coordination). A Cox regression analysis demonstrated that a higher level of ball control was associated with a lower risk to drop-out from table tennis competition. The eye-hand coordination test appeared to be most suitable since it was the only test included in the multivariable Cox regression model (HR = .908; p = .001) (RQ1). Similarly, a multilevel regression analysis showed that a higher level of ball control was associated with a higher future competition performance. The eye-hand coordination and aiming at target tests were included in the multivariable multilevel model (p < 0.05; R2 = 36.4%) (RQ2). This evaluation demonstrates promising prospects for the perceptuo-motor skills assessment to be included in a talent development programme. Future studies are needed to obtain valid thresholds scores and clarify the predictive value in a larger sample of youth competition players.